Mutations on the DNA Binding Surface of TBP Discriminate between Yeast TATA and TATA-Less Gene Transcription - Kamenova, Ivanka (American Society for Microbiology, 2014)
Most RNA polymerase (Pol) II promoters lack a TATA element, yet nearly all Pol II transcription requires TATA binding protein (TBP). While the TBP-TATA interaction is critical for transcription at TATA-containing promoters, it has been unclear whether TBP sequence-specific DNA contacts are required for transcription at TATA-less genes. Transcription factor IID (TFIID), the TBP-containing coactivator that functions at most TATA-less genes, recognizes short sequence-specific promoter elements in metazoans, but analogous promoter elements have not been identified in Saccharomyces cerevisiae. We generated a set of mutations in the yeast TBP DNA binding surface and found that most support growth of yeast. Both in vivo and in vitro, many of these mutations are specifically defective for transcription of two TATA-containing genes with only minor defects in transcription of two TATA-less, TFIID-dependent genes. TBP binds several TATA-less promoters with apparent high affinity, but our results suggest that this binding is not important for transcription activity. Our results are consistent with the model that sequence-specific TBP-DNA contacts are not important at yeast TATA-less genes and suggest that other general transcription factors or coactivator subunits are responsible for recognition of TATA-less promoters. Our results also explain why yeast TBP derivatives defective for TATA binding appear defective in activated transcription.